Metagenomic Analysis of Bacterial Communities in Batik Wastewater from Zie Semarang - Diah Rahma Safitri; R. Susanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aims to analyze the abundance profile, diversity of bacterial communities, and their potential as bioremediation agents in batik wastewater. The research method includes analysis of heavy metal levels (Cr, Pb, Cd, and Cu) using the Atomic Absorption Spectrophotometer (AAS) method and metagenomic analysis based on Next Generation Sequencing (NGS) in the target region V3-V4 of the 16S rRNA gene. The AAS test results showed a chromium (Cr) concentration of 0.035 ppm. The metagenomic analysis results produced alpha diversity, namely the Shannon index of 2.749 and Simpson of 0.865, which means that bacterial diversity is in the moderate category with the dominance of certain groups. The bacterial community was dominated by the phyla Pseudomonadota (62.38%) and Actinomycetota (28.61%), which are known to have high adaptation and tolerance to Cr in degrading organic compounds. At the genus level, the highest percentages were found in Rickettsia (30.2%) and Xanthobacter (24.58%). Xanthobacter has potential as a bioremediation agent, but the presence of Rickettsia needs further study because the sample was mixed with other sources containing Rickettsia vectors. This study provides a basis for optimizing bioremediation by utilizing bacteria that have potential as pollutant degraders based on analysis of previous studies.